S32212, a novel serotonin type 2C receptor inverse agonist/α2-adrenoceptor antagonist and potential antidepressant: II. A behavioral, neurochemical, and electrophysiological characterization. - Dekeyne, A; Brocco, M; Loiseau, F; Gobert, A; Rivet, J; Di Cara, B; Cremers, T; Flik, G; Fone, K; Watson, D; Papp, M; Sharp, T; et al. (2012)
The present studies characterized the functional profile of N-[4-methoxy-3-(4-methylpiperazin-1-yl)phenyl]-1,2-dihydro-3-H-benzo[e]indole-3-carboxamide) (S32212), a combined serotonin (5-HT)(2C) receptor inverse agonist and α(2)-adrenoceptor antagonist that also possesses 5-HT(2A) antagonist properties (J Pharmacol Exp Ther 340:750-764, 2012). Upon parenteral and/or oral administration, dose-dependent (0.63-40.0 mg/kg) actions were observed in diverse procedures. Both acute and subchronic administration of S32212 reduced immobility time in a forced-swim test in rats. Acutely, it also suppressed marble burying and aggressive behavior in mice. Long-term administration of S32212 was associated with rapid (1 week) and sustained (5 weeks) normalization of sucrose intake in rats exposed to chronic mild stress and with elevated levels of mRNA encoding brain-derived neurotrophic factor in hippocampus and amygdala (2 weeks). S32212 accelerated the firing rate of adrenergic perikarya in the locus coeruleus and elevated dialysis levels of noradrenaline in the frontal cortex and hippocampus of freely moving rats. S32212 also elevated the frontocortical levels of dopamine and acetylcholine, whereas 5-HT, amino acids, and histamine were unaffected. These neurochemical actions were paralleled by "promnemonic" properties: blockade of scopolamine-induced deficits in radial maze performance and social recognition and reversal of delay-induced impairments in social recognition, social novelty discrimination, and novel object recognition. It also showed anxiolytic actions in a Vogel conflict procedure. Furthermore, in an electroencephalographic study of sleep architecture, S32212 enhanced slow-wave and rapid eye movement sleep, while decreasing waking. Finally, chronic administration of S32212 neither elevated body weight nor perturbed sexual behavior in male rats. In conclusion, S32212 displays a functional profile consistent with improved mood and cognitive performance, together with satisfactory tolerance.